Ulvan Activates Chicken Heterophils and Monocytes Through Toll-Like Receptor 2 and Toll-Like Receptor 4 - Guriec, Nathalie; Bussy, Frédérick; Gouin, Christelle; Mathiaud, Olivier; Quero, Benoit; Le Goff, Matthieu; Collén, Pi Nyvall (Frontiers in Immunology, 2018)
Responsiveness to invasive pathogens, clearance via the inflammatory response, and activation of appropriate acquired responses are all coordinated by innate host defenses. Toll-like receptor (TLR) ligands are potent immune-modulators with profound effects on the generation of adaptive immune responses. This property is being exploited in TLR-based vaccines and therapeutic agents in chickens. However, for administering the TLR agonist, all previous studies used in ovo, intra-muscular or intra-venous routes that cannot be performed in usual farming conditions, thus highlighting the need for TLR ligands that display systemic immune effects when given orally (per os). Here we have demonstrated that an ulvan extract of Ulva armoricana is able to activate avian heterophils and monocytes in vitro. Using specific inhibitors, we have evidenced that ulvan is a new ligand for TLR2 and TLR4; and that they regulate heterophil activation in slightly different manner. Moreover, activation of heterophils as well as of monocytes leads to release pro-inflammatory cytokines, including interleukin1-β, interferon α and interferon γ, through pathways that we partly identified. Finally, when given per os to animals ulvan induces heterophils and monocytes to be activated in vivo thus leading to a transient release of pro-inflammatory cytokines with plasma concentrations returning towards baseline levels at day 3.